Identification and Genomic Characterization of Two Previously Unknown Magnetotactic Nitrospirae - Zhang, Wensi; Wang, Yinzhao; Liu, Li; Pan, Yongxin; Lin, Wei (Frontiers in Microbiology, 2021)
Magnetotactic bacteria (MTB) are a group of microbes that biomineralize membrane-bound, nanosized magnetite (Fe3O4), and/or greigite (Fe3S4) crystals in intracellular magnetic organelle magnetosomes. MTB belonging to the Nitrospirae phylum can form up to several hundreds of Fe3O4 magnetosome crystals and dozens of sulfur globules in a single cell. These MTB are widespread in aquatic environments and sometimes account for a significant proportion of microbial biomass near the oxycline, linking these lineages to the key steps of global iron and sulfur cycling. Despite their ecological and biogeochemical importance, our understanding of the diversity and ecophysiology of magnetotactic Nitrospirae is still very limited because this group of MTB remains unculturable. Here, we identify and characterize two previously unknown MTB populations within the Nitrospirae phylum through a combination of 16S rRNA gene-based and genome-resolved metagenomic analyses. These two MTB populations represent distinct morphotypes (rod-shaped and coccoid, designated as XYR, and XYC, respectively), and both form more than 100 bullet-shaped magnetosomal crystals per cell. High-quality draft genomes of XYR and XYC have been reconstructed, and they represent a novel species and a novel genus, respectively, according to their average amino-acid identity values with respect to available genomes. Accordingly, the names Candidatus Magnetobacterium cryptolimnobacter and Candidatus Magnetomicrobium cryptolimnococcus for XYR and XYC, respectively, were proposed. Further comparative genomic analyses of XYR, XYC, and previously reported magnetotactic Nitrospirae reveal the general metabolic potential of this MTB group in distinct microenvironments, including CO2 fixation, dissimilatory sulfate reduction, sulfide oxidation, nitrogen fixation, or denitrification processes. A remarkably conserved magnetosome gene cluster has been identified across Nitrospirae MTB genomes, indicating its putative important adaptive roles in these bacteria. Taken together, the present study provides novel insights into the phylogenomic diversity and ecophysiology of this intriguing, yet poorly understood MTB group.